Perlindungan Hukum Terhadap Penerima Gadai Atas Harta Pusako Tinggi yang Dijadikan Jaminan - Debi Riska; Ahmad Muliadi; Nurwidiatmo N (Postgraduate of Jayabaya University, 2019)
High Pusako itself is a treasure obtained from the results of hard work or ancestors in ancient times by mutual cooperation, not assets obtained from grandmother and parents Artati Surya, Cs during his life, so based on customary rules in Minangkabau inheritance it should not be pawned if it is not important, the high property of Pusako must remain intact, because the high property of Pusako will never increase, the existence of these assets to symbolize a people is high pusako. The method used for this research is the normative juridical method. The results of the study To pawn in Bukit Tinggi there are four factors (conditions), namely: Bodies lying in the house, the old girl who is not married, the house is absent, helps the people in distress. Especially in Bukit Tinggi, pawning was found without fulfilling the four factors, because the pledges carried out in general are for education and other needs. and the guarantee of the legal protection of the pawning recipient can be seen in the customary regulations in Minangkabau that high Pusako assets will not be diverted to any party who is not a recipient or heir of high Pusako property so that if someone controls the high property of Pusako because of a pawn they only being able to use the land from the high Pusako property does not make the high propertyof Pusako a permanent ownership.